Non-Suicidal Self-Injury: A School-Based Peer Education Program for Adolescents During COVID-19 Pandemic - Cipriano, Annarosa; Aprea, Cristina; Bellone, Ludovica; Cotrufo, Paolo; Cella, Stefania (Frontiers in Psychiatry, 2022)
Introduction: Non-suicidal self-injury (NSSI) constitutes a major health concern among youth. However, less is known about the useful ways to prevent NSSI. As such, the NSSI- Peer Education Program (NSSI-PEP) aims to intervene on the vulnerability factors that predispose to NSSI by applying a peer education approach. The NSSI-PEP is grounded on the psychoanalytic tradition's tenets, implementing modules targeting four crucial risk factors for NSSI: pubertal transformation, body image, self-esteem, and emotion regulation. Methods: Selected 8th grade students were trained to serve as peer educators and held a peer-education intervention for 6th and 7th grade students. Pre- and post-intervention assessments were conducted in order to evaluate the program's effectiveness. Results: Results revealed preliminary support for the program's feasibility, as students reported greater emotion regulation abilities (p=.038) and significant changes in self-esteem (p<.001), personal alienation (p=.005), body image (p<.001), and maturity fear (p<.001). Also, NSSI-PEP was positively evaluated by participants. Discussion: Our pilot study provides preliminary empirical support for the NSSI-PEP, representing a promising way to address areas of vulnerability for NSSI onset. Findings may also help current policies to promote targeted preventive activities and produce sizable benefits to society.